Nonalcoholic Fatty Liver Diseases in Newly Analyzed Diabetes Mellitus Patients with Risk Factors - Ayzaz Ismail, Jahangir Anjum, Hammad ur Rehman Bhatti, Mazhar Ali Bhutto, Muhammad Azam, Ayesha Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: NAFLD is becoming more common among Asians, as is type-II DM & obesity both of which are connected to fatty liver disease. The goal of the research was to govern the pervasiveness of NAFLD in T2DM patients, as well as their risk factors, in Pakistani population. Materials and Methods: This cross-sectional study was held in the medicine department of Islam Medical and Dental College Sialkot for one-year duration from January 2021 to December 2021. This research included adult individuals who had been diagnosed with T2DM during the previous six months. Ultrasound of the liver was used to detect NAFLD. Measurements that were clinically and biochemically important were completed. Results: NAFLD was detected in 124 T2DM individuals out of a total of 160. (77.5 percent). According to multivariable analysis, NAFLD is associated with dyslipidemia (95 percent, p = 0.035), higher LDL (OR 1.02, p = 0.003), HbA1c (OR1.27, p = 0.045), and diastolic blood pressure (OR 1.05, Hypertension, dyslipidemia, waist circumference, BMI, triglycerides, lack of physical activity, reduced LDL, HDL, ALT and HbA1c all had a combined risk of 11.2 for NAFLD. Conclusion: Numerous lifestyle-related factors have been investigated in connection to a high incidence of NAFLD. It assesses risk factor values to demonstrate the need for NAFLD screening in newly diagnosed DM patients in Pakistan.